Introducing Maya 2008 - Derakhshani, Dariush (Wiley Pub., 2008)
"The new edition of this perennial bestseller is the ideal initiation to 3D and Maya. Starting with the basics, it builds from the ground up, combining straightforward text with practical examples that make it fun and easy to learn Maya's core tools while introducing the latest Maya 2008 features. Follow clear-cut, step-by-step lessons while you learn by doing using a wealth of hands-on files provided on the CD. You'll also find compelling examples in the full-color insert"--Resource description page